Interferon and immunity: the role of microRNA in viral evasion strategies - Bayat, Mobina; Nahid-Samiei, Rahil; Sadri Nahand, Javid; Naghili, Behrouz (Frontiers in Immunology, 2025)
Interferons (IFNs) are indispensable innate antiviral cytokines that orchestrate the vertebrate immune response against viral incursions. Nearly every cell possesses the remarkable ability to release IFNs upon detecting viral threats, triggering a robust signaling cascade that alerts neighboring cells and halts viral propagation via paracrine communication. The intricate influence of IFNs is mediated by an extensive network of proteins activated through the Jak-STAT pathways, facilitating the swift transcription of over 300 interferon-stimulated genes (ISGs) that fortify cellular defenses against replication. However, the cunning nature of viruses has led to the evolution of sophisticated evasion strategies, notably through the manipulation of host microRNAs (miRNAs) that disrupt vital components of the IFN signaling machinery. This review delves into the intricate interplay between viral infections and both host- and viral-derived miRNAs, exploring their potent roles in modulating RIG-I-like receptors, Toll-like receptors, IFN receptors, and the JAK/STAT pathway, ultimately shaping the landscape of antiviral immunity.